Growth and Yield of Urban Farming Water Spinach (Ipomea aquatica) in Different Light Intensity Treatments - Fadila Suryandika; Maryam Eyka Dijono Saputro; Puji Lestari Tarigan; Arul Mordoko (Future Science, 2023)
Water spinach (Ipomea Aquatica) is one of the superior commodities that is often used in urban farming cultivation models. The short lifespan and easy maintenance are the reasons water spinach is chosen for urban farming cultivation. One of the factors that must be considered when cultivating water spinach using urban farming is sufficient sunlight intensity for optimal growth of water spinach. This research aims to analyze the growth and yield of water spinach in the urban farming cultivation model using location placement treatments that have different sunlight intensities. The research method used for analysis of growth and yield which are presented in graphs and analyzed using t-tests. The results of plant growth urban farming water spinach for the parameters of plant height and number of leaves with different treatments of sunlight intensity showed that the values were not significantly different. However, water spinach plants in the unshaded treatment had a higher average plant height and number of leaves than those in the shaded treatment. Meanwhile, the fresh weight and dry weight of water spinach showed that plants with unshaded performance had a higher weight than shaded plants.